Clinical effects and factors associated with adverse clinical outcomes of hymenopteran stings treated in a Thai Poison Centre: a retrospective cross-sectional study - Praopilad Srisuwarn (2022)
Objective: To describe clinical effects and outcomes of hymenopteran stings and to explore the non-laboratory factors associated with adverse clinical outcomes, a composite outcome including death, respiratory failure requiring intubation, acute kidney injury (AKI) requiring dialysis and hypotension requiring vasopressor use. Methods: A retrospective cross-sectional study was performed at the Ramathibodi Poison Center, a poison centre of a tertiary care hospital in Thailand. All cases of hymenopteran sting consultations from January 2015 to June 2019 were consecutively enrolled, and charts were reviewed. Demographics, initial clinical characteristics and outcomes were collected. Factors associated with adverse clinical outcome were explored. Results: One hundred and fourteen hymenopteran stings cases (wasp 48%, bee 33%, hornet 14% and carpenter bee 8.8%) were included (median age, 36.5 years (interquartile range 9–55); male 63%). The prevalence of adverse clinical outcomes was 12.3% (95%CI 6.88–12.8). At initial presentation, 100% of cases had local skin reactions, 11.4% were clinical anaphylaxis, and 8% had red urine. Adverse clinical outcomes included death (n = 10), respiratory failure requiring intubation (n = 9), AKI requiring dialysis (n = 6) and hypotension requiring vasopressor use (n = 2). None of the patients with carpenter bee or hornet stings developed adverse clinical outcomes. In univariable analysis, urticaria, wheezing, red urine, wasp sting and sting number > 10 were significantly associated with adverse clinical outcomes. In multivariable analysis, red urine (adjusted OR 11.1 (95% CI 1.57–216)), wheezing (adjusted OR 16.7 (95% CI 1.43–402)) and a number of stings > 10 (adjusted OR 21.5 (95% CI2.13-2557)) were significant. Conclusions: Adverse clinical outcomes in hymenopteran stings were not uncommon among cases inquiring to a national Thai poison centre. At initial presentation, red urine, wheezing and a number stings >10 were significantly associated with adverse clinical outcomes. Larger epidemiologic studies are required to confirm these associations.